ANALYSIS QUALITY SERVICE, EMOTIONAL AND TRUST CONSUMERS ON CUSTOMER SATISFACTION AT PT. LOLC VENTURA INDONESIA MEDAN - Serina Natasya Pangaribuan; Nurafrina Siregar (RADJA PUBLIKA, 2025)
This research was conducted at PT. Lolc Ventura Indonesia Medan with the aim of the research to analyze the influence of service, emotion and trust on consumer satisfaction in conducting marketing transactions. The population is customers who use the company's services as many as 189 people and sampling with random sampling, namely the Slovin formula so that the number of samples is 65 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques using literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption tests and hypothesis tests. The results of the study show that service, emotional and trust partially and simultaneously have a positive and significant effect on consumer satisfaction. There is a very strong correlation between service, emotional and trust with consumer satisfaction of 65.30% and the remaining 34.70% can be explained by other variables not studied.